Deskriminasi Dalam Novel The Pearl Karya John Steinbeick - Amalia Najwa Sheiland (Fakultas Sastra Universitas Nahdlatul Wathan Mataram, 2022)
This research entitled is “Diskriminasi dalam Novel The Pearl Karya John Steinbeick”. The purpose of this study are to describe any kinds of discrimination that reflected on The Pearl novel. This study used descriptive qualitative method by using sosiological approach to literary works. The data collection techniques that used in this research is literature study. The data used are primary and secondary data from The Pearl novel. Data analysis was carried out by reading and understanding The Pearl novel as a whole, making a synopsis, describing how the describe of discriminations and causative factors itself, and making conclusions. The results of this study show that there’s some kinds of discrimination happened in the novel, discrimination due to racial differences and differences in status or social class.